2011
DOI: 10.1007/s00455-011-9378-5
|View full text |Cite
|
Sign up to set email alerts
|

Dysphagia is a Common and Serious Problem for Adults with Mental Illness: A Systematic Review

Abstract: Adults with mental illness may experience a higher incidence of dysphagia and choking due to factors such as medication side effects and behavioural abnormalities. The aim of this study was to determine the frequency of dysphagia and the most effective interventions for this population. Studies published up to August 2010 were sought via a comprehensive electronic database search (CINAHL, PsycINFO, MEDLINE, PubMed, Cochrane, and Embase). Studies reporting dysphagia frequency or dysphagia intervention outcomes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
34
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 67 publications
0
34
0
Order By: Relevance
“…). Aspiration, weight loss, malnutrition and anxiety are common consequences of dysphagia (Aldridge and Taylor ). Dysphagia is generally classified into two oropharyngeal and esophageal types.…”
Section: Introductionmentioning
confidence: 99%
“…). Aspiration, weight loss, malnutrition and anxiety are common consequences of dysphagia (Aldridge and Taylor ). Dysphagia is generally classified into two oropharyngeal and esophageal types.…”
Section: Introductionmentioning
confidence: 99%
“…They speculated that the cause may be hyperverbosity. A recent systematic review of 10 studies revealed that the frequency of dysphagia in adults with mental illness was 9 to 46%, compared to 6% in the general population [3]. Causes may be multifactorial, including behavioural and pharmacological.…”
Section: Discussionmentioning
confidence: 99%
“…Our patient appears to have had recurrent aspiration pneumonia in association with manic episodes. There is no current guidance on interventions in managing dysphagia in adults with mental health illness [3]. …”
Section: Discussionmentioning
confidence: 99%
“…A role statement also assists in establishing professional boundaries, which is useful when advocating for and explaining the role of APDs to other health professionals. In the case of mental health, for example, higher rates of dysphagia have been reported: 12,13 assessing swallowing difficulties is a speech pathologist's (SP's) role, while APDs have a role to work with SPs in managing any necessary diet prescriptions. It should be pointed out that a role statement is not designed to be a set of practice guidelines, entry-level standards or training recommendations for dietitians working in mental health.…”
mentioning
confidence: 99%